2011
DOI: 10.1111/j.1549-8719.2011.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Blood Flow Analysis Detects Microvascular Abnormalities in Impaired Glucose Tolerance

Abstract: Analysis of ocular Doppler flow waveforms using the discrete wavelet transform identified microvascular abnormalities that were not apparent using RI. Pioglitazone improved glucose, insulin sensitivity, and triglycerides without influencing the contour of the waveforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…This finding is in contrast to other studies demonstrating that WT analysis is superior in detecting microvascular abnormalities in other vascular beds such as the retinal circulation [16,20]. This finding may be the consequence of the post-processing process required to undertake WT analysis in the current work.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This finding is in contrast to other studies demonstrating that WT analysis is superior in detecting microvascular abnormalities in other vascular beds such as the retinal circulation [16,20]. This finding may be the consequence of the post-processing process required to undertake WT analysis in the current work.…”
Section: Discussioncontrasting
confidence: 55%
“…This approach yields information such as RI, PI, notches, troughs and peaks which does not permit a comprehensive analysis of Doppler flow velocities over the entire cardiac cycle. This approach fails to identify significant changes in the waveform contour that may be indicative of structural or functional changes in downstream vascular beds [14,19,20]. The precise physiological origin of these features on waveforms has proved difficult to elucidate, but it is widely appreciated that such approaches ignore the vast majority of information contained in the signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were included as comparators in this study as they are widely quoted and understood, being often displayed directly on ultrasound scanner screens now. These measures have been used extensively in the analysis of Doppler blood flow waveforms and yet their limitations have been equally well documented [ 12 , 15 - 19 ]. As single domain methods, it has been suggested that they lack the necessary flexibility to adequately assess an entity as variable as the blood flow waveform.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Interventions on the life of people with IGT could delay the onset of type 2 diabetes, reduce microvascular complications, the incidence of cardiovascular and all-cause mortality, and extend life expectancy. 3,4 It was known that IGT could cause changes in renal microcirculation, [5][6][7] retinal microcirculation, 8 myocardial microcirculation 9 and skeletal muscle perfusion. 9,10 However, as far as the authors were concerned, there was no relevant report on foot microcirculation of IGT patients.…”
Section: Introductionmentioning
confidence: 99%